PbS additive modified AgO positive electrode material, preparation method and zinc-silver battery

By introducing PbS into the positive electrode material AgO of zinc-silver battery and generating PbSO4, the problem of short storage life of zinc-silver battery caused by AgO decomposition is solved, and the effect of extending the storage life of the battery and improving stability is achieved.

CN119560526AActive Publication Date: 2025-03-04BEIJING INST OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411665285.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-04
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The storage life of zinc-silver batteries is limited, mainly due to the decomposition of the positive electrode material AgO, the oxidation of the negative electrode plate active material Zn, and the degradation of the separator performance, which affects the stability and service life of the battery during long-term storage.

Method used

By introducing the metal sulfide additive PbS into the AgO positive electrode material and being ball milled and mixed to generate PbSO4, the decomposition of AgO is suppressed and its stability is improved.

Benefits of technology

It effectively inhibits the decomposition of AgO during ball milling and aging, extends the storage life of zinc-silver batteries, and improves its stability during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560526A_ABST
    Figure CN119560526A_ABST
Patent Text Reader

Abstract

The invention relates to a PbS additive modified AgO positive electrode material, a preparation method and a zinc-silver battery, and belongs to the technical field of zinc-silver batteries. The mass of the PbS is 1%-5% of that of the AgO positive electrode material, and the composite material is prepared by wet mixing and ball milling. PbS is added into the AgO positive electrode material, and PbSO4 is generated after ball milling, so that the decomposition of AgO in the ball milling process can be inhibited, and the decomposition of AgO in the aging process can also be inhibited. The positive electrode material can be stored in the zinc-silver battery for a long time, so that the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a PbS additive-modified AgO positive electrode material, a preparation method and a zinc-silver battery, and belongs to the technical field of zinc-silver batteries. Background Art

[0002] Zinc-silver batteries have been widely used and deeply studied in various fields due to their high specific energy, stable discharge voltage and good safety. However, with the continuous advancement and iteration of equipment technology, these devices not only have more advanced performance, but also increasingly stringent requirements for supporting energy systems. Especially for equipment that needs to be on standby for a long time or perform long-distance missions, such as satellite platforms, deep-sea probes and certain special-purpose missile systems, the storage life of their built-in batteries has become a key factor restricting overall performance and cost-effectiveness. Therefore, extending the storage life of zinc-silver batteries and ensuring that they can provide stable and reliable power support throughout the mission cycle has become an urgent need in the current zinc-silver battery research and development field.

[0003] The main reasons for the limited storage life of zinc-silver batteries are: ① Decomposition of positive electrode AgO: During storage, the positive electrode material AgO is prone to decomposition reactions to generate Ag2O and O2, resulting in a reduction in active substances, which in turn affects the discharge performance and service life of the battery. This is the most important factor limiting the storage life of zinc-silver batteries; ② Oxidation of the negative electrode plate active material Zn: During storage, Zn reacts with oxygen, moisture, etc. in the environment, resulting in oxidation, reducing the effective active substances in the negative electrode, further shortening the storage life of the battery; ③ Degradation of diaphragm performance: As a key component inside the battery, the performance of the diaphragm may gradually decline over time, affecting the stability of the electrolyte and the control of the internal reactions of the battery, thereby indirectly shortening the storage life of the battery. Therefore, there is an urgent need for a method to improve the stability of AgO to extend the storage life of zinc-silver batteries. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a PbS additive-modified AgO positive electrode material, a preparation method and a zinc-silver battery. The metal sulfide additive PbS is introduced into the positive electrode material for modification to inhibit the decomposition of AgO, thereby facilitating the improvement of the stability of the zinc-silver battery during long-term storage and extending the storage life.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows.

[0006] A PbS additive-modified AgO positive electrode material, wherein the mass of PbS is 1% to 5% of the mass of the AgO positive electrode material, and PbS and the AgO positive electrode material are mixed by ball milling to generate PbSO4, which inhibits the decomposition of AgO.

[0007] Preferably, the mass of the PbS is 2.5% to 3.5% of the mass of the AgO positive electrode material.

[0008] Preferably, taking the total mass of the AgO positive electrode material as 100%, the raw material components and their mass percentages are AgO 90% to 95%, Ag2O 1% to 4%, and Ag 4% to 6%.

[0009] A method for preparing the PbS additive-modified AgO positive electrode material of the present invention, the method steps comprising:

[0010] The PbS and AgO positive electrode materials are mixed, and an organic solvent is added to wet ball mill at 200-400 r / min for 3-12 hours. After the ball milling is completed, the mixture is dried by forced air at 50-60° C. for 8-12 hours to obtain a PbS additive-modified AgO positive electrode material.

[0011] Preferably, during wet ball milling, the diameter of the ball milling beads is 6 to 10 mm.

[0012] Preferably, during wet ball milling, the organic solvent is cyclohexane, tetrahydrofuran, acetonitrile or isopropanol, more preferably isopropanol.

[0013] A zinc-silver battery, wherein the positive electrode material of the battery is the AgO positive electrode material modified by a PbS additive described in the present invention.

[0014] Beneficial Effects

[0015] In the present invention, PbS is added to the AgO positive electrode material to generate PbSO4 after ball milling, which can not only inhibit the decomposition of AgO during the ball milling process, but also inhibit the decomposition of AgO during the aging process. The positive electrode material can extend the service life of the zinc-silver battery during long-term storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the SEM image of the positive electrode material of Comparative Example 1.

[0017] Figure 2 This is the SEM image of the positive electrode material in Comparative Example 2.

[0018] Figure 3 This is the SEM image of the positive electrode material in Example 1.

[0019] Figure 4 2 is the XRD diagram of the positive electrode material in Examples 1-2 and Comparative Example 1.

[0020] Figure 5 This is the XRD diagram of the positive electrode material in Comparative Examples 1-3.

[0021] Figure 6 TG diagrams of the positive electrode materials in Example 1 and Comparative Example 2.

[0022] Figure 7 TG diagram of the positive electrode materials in Example 2 and Comparative Example 3.

[0023] Figure 8 Ag 3d and O1s diagrams fitted according to XPS tests of the positive electrode materials in Comparative Examples 2-3 and Examples 1-2.

[0024] Fig. 9 It is a diagram showing the proportions of AgO, Ag2O, and Ag calculated based on the Ag 3d spectra of Comparative Examples 2-3 and Examples 1-2.

[0025] Fig.10 It is the Pb 4f diagram fitted according to the XPS test of the positive electrode material in Example 1-2.

[0026] Fig.11 It is the S2p diagram fitted according to the XPS test of the positive electrode material in Example 1-2. DETAILED DESCRIPTION

[0027] The present invention will be further described in detail below in conjunction with specific embodiments.

[0028] In order to verify the extended storage life of the modified AgO positive electrode, an AgO electrode stored for 14 years was obtained by a high-temperature accelerated storage experimental method. The high-temperature accelerated storage method of the present invention is to place the material in a vacuum oven at 70°C for 256 hours. The principle is:

[0029] The aging and accelerated aging processes of the main component AgO in the AgO positive electrode material at room temperature, and the decomposition kinetic equations are:

[0030] K1=A1exp(-E a1 / RT1) (1)

[0031] K2=A2exp(-E a2 / RT2) (2)

[0032] Where E a =116.56KJ mol -1 , A=17.20s -1 .

[0033] Due to the E corresponding to the decomposition reaction of AgO at different temperatures a It is not much different from A, so we have:

[0034]

[0035] Therefore, when T1 = 298K (25°C) and T2 = 343K (70°C), the corresponding value of the reaction rate constant K2 / K1 is 479.25.

[0036] For the solid phase reaction 2AgO+Ag→Ag2O, the relationship between the equilibrium constant and the storage time at a certain temperature is:

[0037]

[0038] Where n is the number of sample storage temperature sections, m i0 is the initial mass of the sample in the i-th section, m i is the mass after the end of storage in the i-th stage, t i is the storage time. Under constant temperature conditions, K = (m0-m) / t. Since the initial mass is the same, the value of (m0-m) corresponding to the same retention rate is the same when decomposed. From formula (4), we can get t1 / t2 = K2 / K1. For the positive electrode stored for 14 years, t1 is 5110 days, and t2 = 10.66 days.

[0039] Therefore, placing the positive electrode material in a vacuum oven at 70°C for 256 hours can achieve the result of storing it at room temperature for 14 years.

[0040] SEM characterization: Instrument: FEI-Quanta 250 from Thermo Fisher Scientific, Voltage: 25 kV.

[0041] XRD characterization: Instrument: Rigaku's Ultima IV, scanning angle: 10-80°, scanning speed: 5° / min.

[0042] TG characterization: Instrument: WCT-D of Beijing Beiguang Century Instrument Co., Ltd., heating rate: 5°C / min, temperature range: 30°C~800°C.

[0043] XPS characterization: Instrument: PHIQUANTERA-II SXM from ULVAC-PHI, Japan.

[0044] Example 1

[0045] (1) Preparation of positive electrode materials: According to the ratio of 90.21% by mass of AgO, 2.82% by mass of Ag2O, 3.97% by mass of Ag, and 3.0% by mass of PbS, 0.9021 g of AgO, 0.0282 g of Ag2O, 0.0397 g of Ag, and 0.0300 g of PbS were weighed, put into a mortar and ground for about 30 min, and mixed evenly.

[0046] (2) Ball milling: Add 6 mm diameter ball milling beads that occupy 2 / 3 of the volume of the ball milling jar, put the mixed positive electrode material into the ball milling jar, add 5 mL of isopropanol as solvent, and ball mill for 3 h at a speed of 200 r / min.

[0047] (3) Drying: The ball-milled material was collected and placed in a forced air drying oven at 50° C. for 8 to 12 h to obtain a PbS additive-modified AgO positive electrode material.

[0048] Example 2

[0049] The AgO positive electrode material modified with the PbS additive obtained in Example 1 was placed in a vacuum oven at 70° C. for 256 hours.

[0050] Comparative Example 1

[0051] (1) Preparation of positive electrode material: 0.9300 g of AgO, 0.0290 g of Ag2O and 0.0410 g of Ag were weighed according to the ratio of 93.00% by mass of AgO, 2.90% by mass of Ag2O and 4.10% by mass of Ag, put into a mortar and grind for about 30 min, mix well, and obtain an AgO positive electrode material.

[0052] Comparative Example 2

[0053] (1) Preparation of positive electrode materials: 0.9300 g of AgO, 0.0290 g of Ag2O and 0.0410 g of Ag were weighed according to the ratio of 93.00% by mass of AgO, 2.90% by mass of Ag2O and 4.10% by mass of Ag, put into a mortar and grind for about 30 min to mix well.

[0054] Steps (2)-(3) are the same as in Example 1 to obtain an AgO positive electrode material.

[0055] Comparative Example 3

[0056] (1) The dried material in Comparative Example 2 was placed in a vacuum oven at 70° C. for 256 hours.

[0057] The SEM test results of the positive electrode materials described in Comparative Examples 1-2 and Example 1 are as follows: Figure 1-3 As shown, the material particles without ball milling in Comparative Example 1 are uniform in size and evenly distributed; the material particles after ball milling in Comparative Example 2 are broken, the particle size becomes smaller, but there is obvious agglomeration; the material particles after ball milling with PbS in Example 1 are relatively uniform, with slight agglomeration. This shows that PbS has a certain improvement on the damage of material morphology caused by ball milling.

[0058] The XRD test results of the positive electrode materials described in Comparative Examples 1-3 and Examples 1-2 are as follows: Figure 4-5 As shown, compared with the positive electrode material in Comparative Example 2, strong diffraction peaks were observed at 2θ of 32.01°, 32.28°, 34.17°, 37.18° and 39.38°, corresponding to the (200), (111), (002), (111) and (202) crystal planes of AgO (PDF#43-1038), while the diffraction peak intensity of Comparative Example 3 was significantly weakened, indicating that AgO decomposed during the aging process; compared with Example 1, the diffraction intensity of the (111) crystal plane of AgO in the material described in Example 2 was weakened to a certain extent, while the diffraction intensity of other crystal planes changed slightly, proving that PbS has a certain inhibitory effect on the decomposition of AgO during the aging process.

[0059] The inhibition effect was further quantitatively verified by TG test. The TG test results of the positive electrode materials described in Comparative Examples 1-3 and Examples 1-2 are as follows: Figure 6-7 As shown in Table 1, the proportion of AgO, Ag2O and Ag in the material can be calculated by the weight loss rate of the two platforms, as shown in Table 1. In Example 1, after PbS was introduced into the AgO positive electrode material, the proportion of AgO increased from 55.80% to 73.32%, indicating that the introduction of PbS inhibited the decomposition of AgO during ball milling. In order to quantitatively describe the inhibitory effect of the introduction of PbS on the decomposition of AgO, the retention rate of the AgO ratio after aging compared with that before aging was calculated, as shown in Table 2. The retention rate of AgO increased from 82.50% to 87.52%, indicating that the introduction of PbS inhibited the decomposition of AgO during the aging process, which is mutually confirmed by the results of XRD.

[0060] Table 1

[0061]

[0062] Table 2

[0063]

[0064] XPS test was performed on the materials of Comparative Example 2-3 and Example 1-2. The fitting spectra of Ag 3d and O1s are as follows: Figure 8 As shown, the Ag element exists in the material mainly in the form of +3 valence, +1 valence and 0 valence; the O element exists in the material mainly in the form of metal-oxygen bond (MO bond), and the other part of the O element exists in the form of Ag-O2. This is because the existence of Ag alone will combine with O2 in the air. Although XPS, as a semi-quantitative surface analysis technology, cannot accurately reflect the true composition of the material, it can still effectively reveal the overall trend and serve as an auxiliary verification method for TG test results. By analyzing the ratio of Ag in different valence states in the XPS total spectrum, the relative contents of AgO, Ag2O and single Ag are calculated and plotted into a bar graph. The results are shown in Fig. 9 Basically consistent with the TG test results, the proportion of AgO in the positive electrode material described in Example 1 increased significantly, indicating that the introduction of PbS helps to inhibit the decomposition of AgO during the ball milling process and the aging process; and the proportion of AgO in the aged material in Example 2 is higher than that in the aged material in Comparative Example 3, proving that the introduction of PbS helps to inhibit the decomposition of AgO during the aging process.

[0065] Based on the above analysis, the introduction of PbS helps to inhibit the decomposition of AgO during ball milling and aging.

[0066] The XPS fitting results of Pb 4f and S2p in the material after the introduction of PbS are as follows: Fig.10 and Fig.11 As shown in the figure, according to the fitting results, Pb has characteristic peaks at 137.8eV and 142.6eV, corresponding to Pb-O bond and Pb-S bond, while S has obvious characteristic peaks at 163.4eV and 168.4eV, corresponding to S-Pb bond and SO bond. This indicates that the introduction of PbS generates PbSO4 after ball milling, and this product plays a role in inhibiting the decomposition of AgO during the ball milling process and aging process.

[0067] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A PbS additive-modified AgO positive electrode material, characterized in that: The mass of PbS is 1% to 5% of the mass of the AgO positive electrode material. PbS and the AgO positive electrode material are mixed by ball milling to generate PbSO4, which inhibits the decomposition of AgO.

2. The PbS additive-modified AgO positive electrode material according to claim 1, characterized in that: The mass of the PbS is 2.5% to 3.5% of the mass of the AgO positive electrode material.

3. A PbS additive-modified AgO positive electrode material according to claim 1 or 2, characterized in that: Taking the total mass of the AgO positive electrode material as 100%, the raw material components and their mass percentages are AgO 90% to 95%, Ag2O 2% to 4%, and Ag 4% to 6%.

4. A method for preparing a PbS additive-modified AgO positive electrode material according to any one of claims 1 to 3, characterized in that: The method steps include: The PbS and AgO positive electrode materials are mixed, and an organic solvent is added to wet ball mill at 200-400 r / min for 3-12 hours. After the ball milling is completed, the mixture is dried by forced air at 50-60° C. for 8-12 hours to obtain a PbS additive-modified AgO positive electrode material.

5. The method for preparing a PbS additive-modified AgO positive electrode material according to claim 4, characterized in that: During wet ball milling, the diameter of the ball milling beads is 6 to 10 mm.

6. The method for preparing a PbS additive-modified AgO positive electrode material according to claim 4, characterized in that: During wet ball milling, the organic solvent is cyclohexane, tetrahydrofuran, acetonitrile or isopropanol.

7. The method for preparing a PbS additive-modified AgO positive electrode material according to claim 6, characterized in that: The organic solvent is isopropanol.

8. A zinc-silver battery, characterized in that: The positive electrode material of the battery is a PbS additive-modified AgO positive electrode material as claimed in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Pole piece protecting method for prolonging dry storage life of zinc-silver battery

    CN103050718A

  • Zinc-silver battery and high-specific-capacity AgO positive electrode material thereof

    CN115849431A

  • Process for producing divalent silver oxide cathode material

    EP0117902A1

  • Improvements relating to Active Material for Alkaline Electric Batteries

    GB1178918A

  • Mixture for zinc electrode

    JP2015197976A